TEACHERS' CHALLENGES IN PREPARING LEARNING MATERIALS IN ONLINE TEACHING FOR VOCATIONAL STUDENTS - Febriana Widyastuti, - (2021)
Conventional offline face-to-face learning has been substituted for online practice during this pandemic. The sudden change to the online classroom has raised challenges for teachers in preparing online learning materials for vocational classrooms. This case study research investigates the challenges teachers face and their responses to challenges in preparing online learning materials for vocational classrooms. By involving four teachers from the research site as participants, the data were gathered from the semi-structured interviews and learning materials documents used in classrooms. The semi-structured interviews were analyzed by adapting Mayring's (2000) inductive analysis framework, while the documents were analyzed using Hutchinson and Water's (1987) materials evaluation framework. The results reveal that teachers faced three kinds of problems in preparing online learning materials for vocational high school, namely, (1) challenges related to students' availability to access materials, (2) teachers' internal challenges to ESP and technology skills, (3) educational policies. Furthermore, in order to solve these problems, participants reported that they tried to create learning materials that consume low internet usage, learn how to use technology, learn about vocational content, and try to create learning materials that could accommodate the limited period of online meeting. This study also shows that the EFL online learning materials prepared in that school have partially met the course objectives, but not the vocational content. Therefore, it is essential to equip EFL vocational classroom teachers with adequate ESP skills and to create a standard of EFL learning materials for vocational high schools to solve those challenges in the future.